Geometric morphometric analysis of the brainstem and cerebellum in Chiari I malformation - Perera, Ishan R.; Zahed, Malek; Moriarty, Sydney; Simmons, Zachary; Rodriguez, Maya; Botkin, Courtney; Dickson, Taylor; Kasper, Bradley; Fahmy, Kendyl; Millard, Jonathan A. (Frontiers in Neuroanatomy, 2024)
Background Chiari I malformation (CMI) is characterized by inferior descent of the cerebellar tonsils through the foramen magnum and is associated with headache and neck pain. Many morphometric research efforts have aimed to describe CMI anatomy in the midsagittal plane using classical measurement techniques such as linear dimensions and angles. These methods are less frequently applied to parasagittal features and may fall short in quantifying more intricate anatomy with fewer distinct homologous landmarks. Methods Landmark-based geometric morphometric techniques were used to asses CMI morphology in five anatomical planes of interest. Results Significant shape differences between CMI and age/sex-matched controls were found in the midsagittal (Pseudo-F = 5.4841, p = 0.001) and axial planes through the rostral medulla (Pseudo-F = 7.6319, p = 0.001). In addition to tonsillar descent, CMI principal component 1 (PC1) scores in the midsagittal protocol were associated with marked anterior concavity of the brainstem and generalized verticality of the cerebellum with anterior rotation of its anterior lobe. In the axial medulla/cerebellum protocol, CMI PC1 scores were associated with greater anterior–posterior (A-P) dimension with loss of medial-lateral (M-L) dimension. Discussion These results suggest that CMI is associated with greater curvature of the brainstem and spinal cord, which may perturb normal neural activities and disrupt cerebrospinal fluid movements. Previous reports on the A-P diameter of the posterior fossa in CMI have conflicted; our findings of greater A-P cerebellar dimensionality with concomitant loss of width alludes to the possibility that more caudal aspects of the posterior cranial fossa are more bowl-like (homogenous in axial dimensions) and less trough-like or elongated in the M-L direction.